The influence of leadership communication on organization commitment among non-academic staff in UiTM Samarahan / Atikawati Ahmad Razali - Ahmad Razali, Atikawati (2015)
Organizational commitment (OC) has important implications on employees and organizations as confirmed by past researchers. Leadership communication style also play an important role in this study because it has been proved by past researcher that communication and leadership style comes together and completing each other. They work hand in hand to ensure the successful and effectiveness of an organization. This study examines leadership communication styles and employees’ organizational commitment in the UiTM Samarahan context. Three types of leadership communication styles namely core, managerial and corporate leadership communication styles have been chosen as focus of research to investigate the impact on organizational commitment. This is imperative in order to ensure the successful management of employees and also to improve productivity and achievements of an organization. There are 190 non-academic supporting staff voluntarily participated in this study. The results have indicated that several dimensions of core, managerial and corporate leadership communication have positive relationship with organizational commitment. Implications of the findings, potential limitations of the study and directions for future research are suggested.